If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3-x+6/6=4x
We move all terms to the left:
3-x+6/6-(4x)=0
We add all the numbers together, and all the variables
-5x+4=0
We move all terms containing x to the left, all other terms to the right
-5x=-4
x=-4/-5
x=4/5
| 9a+6=96 | | 3-(x+6)/6=4x | | 4y-11=256 | | x+35=18 | | 12×1.17 t = 56. | | 24.3=x^2 | | 9z/12=8z/12+15 | | 9p2=6(p+20 | | F(x)=-16x^2+12x | | 36=-x^2-12x+32 | | 6a-6=78 | | 100-n=47 | | 3/1-2x-3/4=2x/1-3/2 | | 12-3x^2=36 | | 26=5+3x÷4 | | 26=5+3x/4 | | 2x+21=39-5x | | 13=8+5(2x-7) | | 6w+2=20 | | 16x/x=40/25 | | -2x+18=16 | | 8x+12=3x+52 | | -4x-9=-x-24 | | 2(3x+2)+5=3x/2 | | 26.32x=114-114x | | 2x(5-2)+48-42+4=32 | | 6+X=0.2x | | (x/x)=5.86666666667 | | -12=(3-x)*4 | | 4a-4=33 | | 2x+5+5x=45-x | | 0.02a=0.1 |